Manajemen Daya Listrik dengan Sistem Automatic Transfer and Synchronization Switch berbasis PLC - Supriono; Seno D. Panjaitan (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2015)
In the current electric energy supply crisis, Indonesian Government encourages the citizen to save electric energy. Therefore, we should control the electric power consumption in the offices or houses intelligently. Using one of automation technologies, Programmable Logic Controller (PLC), we can control electricity usage in our surroundings. This research focuses on the development of Automatic Transfer Switch (ATS) system to become Automatic Transfer and Synchonization Switch (ATSS). The system can monitor electric power consumption connected to PLN. If the electric power consumption has reached > 80%, then the generator as electric energy back up supply will support in a synchronized way. If electric power load is < 80% then automatically the generator is non-active. ATSS can become an ATS as well. It is an electric energy back up power supply when supply from PLN is cut. The result shows that a 900 watt electric power PLN, with 1.060 watt maximum load, and 300 watt support generator synchonization, can support a load of 1.450 watt.